The staging and grading system in defining periodontitis cases: consistency and accuracy amongst periodontal experts, general dentists and undergraduate students. (14th December 2020) - Marini, Lorenzo; Tonetti, Maurizio S.; Nibali, Luigi; Rojas, Mariana A.; Aimetti, Mario; Cairo, Francesco; Cavalcanti, Raffaele; Crea, Alessandro; Ferrarotti, Francesco; Graziani, Filippo; Landi, Luca; Sforza, Nicola M.; et al.
Abstract: Aim: The objective of this study was to evaluate consistency and accuracy of the periodontitis staging and grading classification system. Methods: Thirty participants (10 periodontal experts, 10 general dentists and 10 undergraduate students) and a gold‐standard examiner were asked to classify 25 fully documented periodontitis cases twice. Fleiss kappa was used to estimate consistency across examiners. Intraclass correlation coefficient (ICC) was used to calculate consistency across time. Quadratic weighted kappa and percentage of complete agreement versus gold standard were computed to assess accuracy. Results: Fleiss kappa for stage, extent and grade were 0.48, 0.37 and 0.45 respectively. The highest ICC was provided by students for stage (0.91), whereas the lowest ICC by general dentists for extent (0.79). Pairwise comparisons against gold standard showed mean value of kappa >0.81 for stage and >0.41 for grade and extent. Agreement with the gold standard for all three components of the case definition was achieved in 47.2% of cases. The study identified specific factors associated with lower consistency and accuracy. Conclusions: Diagnosis was highly consistent across time and moderately between examiners. Accuracy was almost perfect for stage and moderate for grade and extent. Additional efforts are required to improve training of general dentists.